Nanoscale Polishing of TC4 Titanium Alloy Surface Based on Dual-Pole Magnetic Abrasive Finishing Method - Zhenfeng Zhou; Xu Sun; Shibing Liang; Ying Fang; Yanzhen Yang; Yongjian Fu; Shiqing Zou (Micromachines, 2025)
The dual-pole magnetic abrasive finishing (DMAF) method was proposed to achieve a smooth surface on TC4 titanium alloy. Firstly, both the distribution of the magnetic field and the intensity of magnetic induction produced by nine combinations of magnetic poles of different shapes were simulated using Ansys Maxwell software (2024R2). According to the results of the simulation, the optimal combination of magnetic poles was determined. Then, the machining parameters of multi-stage DMAF were optimized through comparative experiments on major single factors. Finally, combinations of the mixed magnetic abrasive in three polishing stages were obtained as follows: #100 electrolytic iron powder (Fe3O4) + #2000 white abrasive (WA), #200 Fe3O4 + #8000 WA, and #450Fe3O4 + #w1 diamond (DMD). The gap between the upper and lower magnetic poles was set to 5 mm, the rotational speed of the magnetic pole was set to 300 rpm, and the quality ratio of the abrasive was 2:1. The experiments indicated that the average surface roughness Ra was reduced from an initial value of 0.433 μm to 8 nm after 30 min of multi-stage DMAF, and a nano-level mirror polishing effect was essentially achieved in the polishing zone.